Fluorinated Nanocomposite Coatings for Confinement and Pumpless Transport of Low‐Surface‐Tension Liquids. Issue 19 (18th August 2019) - Morrissette, Jared M.; Ghosh, Aritra; Campos, Raymond; Mates, Joseph E.; Mabry, Joseph M.; Megaridis, Constantine M.
Abstract: Preparing surfaces that repel low‐surface‐tension liquids, such as oils and hydrocarbon fuels with surface tensions below 30 mN m −1, poses more challenges than attaining water repellency. Oleophobic surfaces are needed when organic fluids must be contained to avoid pollutant spreading. A composite material system is presented comprised of fluorinated silica (filler), a perfluoroalkyl methacrylate copolymer (binder), and fluorinated polyhedral oligomeric silsesquioxane (additive; considered the lowest surface‐energy material to date), which can be applied as a thin coating onto any substrate. The coating is shown to repel liquids with surface tension as low as 23.8 mN m −1 . Regions of the coatings are made superoleophilic (high affinity to oils and other hydrocarbons) through laser processing, thus generating wettability‐patterned surfaces that can passively manage and transport low‐surface‐tension liquids by harnessing forces arising from the spatial confinement of the fluid. The rapid (>20 cm s −1 ) pumpless transport of several liquid hydrocarbons on open‐air, wettability‐engineered surfaces is demonstrated, and the respective transport rates are compared to those of water. The sprayable coating formulation and post‐processing steps used in this work offer a tractable approach to rapidly fabricate and test wettability‐engineered devices that can effectively contain, manage, and pumplessly transport low‐surface‐tension liquids on open surfaces. Abstract : A composite coating consisting of fluorinated silica (filler), a perfluoroalkyl methacrylate copolymer (binder), and fluorinated polyhedral oligomeric silsesquioxane (additive), is shown to repel organic liquids with surface tension as low as 23.8 mN m −1 . Wettability‐engineered tracks using this material can transport low‐surface‐tension liquids pumplessly on open surfaces with speeds exceeding 0.2m s −1 .